Zapomniane karty z dziejów rosyjskich czasopism dla kobiet początku XIX wieku (wokół inicjatyw wydawniczych Michaiła Makarowa i Piotra Szalikowa) - Dąbrowska, Magdalena (Rusycystyczne Studia Literaturoznawcze, 2015)
The subject of the article is the connections of Mikhail Makarov and Peter Shalikov (and also Anna Bunin and Elizaveta Trubieсkaya?) with the periodicals for women “Amur” and “Damski zhournal”. “Amur” — the unrealized initiative from 1805 or 1806. “Damski zhournal” — the literary periodical of sentimental tendencies. In the article there are discussed the memories of Stepan Zykhariov (The student’s notes…), Mikhail Dmitriev (The Bits and Pieces from my Memories) and Phillip Wigiel (The memories). In their writings Makarov and Shalikov merge the 18th century with the first half of the 19th century.